THE EFFECT OF TRASH FISH FEED TYPE ON ABSOLUTE WEIGHT GROWTH OF RICE FIELD EEL (Monopterus albus) SIZE 12-15 cm IN EXPERIMENTAL TANKS - Totok Hariyanto; Muhajir Muhajir; Ir. Indra Wirawan (Universitas Mataram, 2025)
The rice paddy eel (Monopterus albus) is a freshwater fishery commodity of high economic value and is widely favored by Indonesian consumers. This species has the ability to breathe through its skin and gills, allowing it to survive in environments with low oxygen levels, enabling cultivation in muddy waters, swamps, and rice fields with minimal water quality conditions. The growth of rice paddy eels is strongly influenced by seed size and the type of feed provided. Eels measuring 12–15 cm can be fed either natural or commercial feed, although the use of commercial feed is considered less relevant due to its high price, despite its complete nutritional composition. An alternative feed source is trash fish, a type of marine fish waste containing adequate nutritional value and potentially supporting growth efficiency. This study aimed to determine the effect of different types of trash fish feed on the absolute weight growth of rice paddy eels measuring 12–15 cm in experimental tanks. The research was conducted using an experimental method with a Completely Randomized Design (CRD), consisting of three treatments and nine replications. The treatments included the administration of different species of trash fish: Treatment A using tembang fish, Treatment B using trevally fish, and Treatment C using petek fish. Rice paddy eels used as test organisms had an initial average weight of 5 g/individual and were stocked at a density of three individuals per 0.5 m². The experimental tanks were filled with freshwater at a depth of 10 cm. The results showed that Treatment B produced the highest increase in absolute weight growth, reaching 3.37 g/individual. Water quality parameters during the experiment remained within optimal ranges for eel cultivation, with temperatures of 27.1–27.7 °C, pH values of 6.7–7.1, and dissolved oxygen levels of 5.32–5.61 ppm, indicating suitable conditions for growth.